Onco-miR-24 regulates cell growth and apoptosis by targeting BCL2L11 in gastric cancer - Haiyang Zhang; Jingjing Duan; Yanjun Qu; Ting Deng; Rui Liu; Le Zhang; Ming Bai; Jialu Li; Tao Ning; Shaohua Ge; Xia Wang; Zhenzhen Wang; et al. (Protein & Cell, 2016)
ABSTRACT Gastric cancer is one of the most common malignancies worldwide; however, the molecular mechanism in tumorigenesis still needs exploration. BCL2L11 belongs to the BCL-2 family, and acts as a central regulator of the intrinsic apoptotic cascade and mediates cell apoptosis. Although miRNAs have been reported to be involved in each stage of cancer development, the role of miR-24 in GC has not been reported yet. In the present study, miR-24 was found to be up-regulated while the expression of BCL2L11 was inhibited in tumor tissues of GC. Studies from both in vitro and in vivo shown that miR-24 regulates BCL2L11 expression by directly binding with 3′UTR of mRNA, thus promoting cell growth, migration while inhibiting cell apoptosis. Therefore, miR-24 is a novel onco-miRNA that can be potential drug targets for future clinical use.